2009
DOI: 10.1097/inf.0b013e318198d05c
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection of Parvovirus B19 With Other Hepatitis Viruses Leading to Fulminant Hepatitis of Unfavorable Outcome in Children

Abstract: Fulminant hepatic failure (FHF) associated with parvovirus B19 (B19) infection has a favorable prognosis in children. However, there is no data available to predict outcome in cases of FHF associated with hepatotropic virus coinfection. Clinical characteristics of 3 pediatric groups with FHF were compared and it was observed that B19 coinfection with other viruses adds to the severity of the disease and increases the probability of a fatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Dwivedi et al in their study of 48 patients with FHF, divided them into three groups as those associated with (i) B19 infection alone, (ii) one or more other hepatotropic viral infection in the absence of B19 infection, and (iii) B19 coinfection with other hepatotropic viruses. They found that FHF caused by B19 and coinfection with other hepatitis viruses had severe jaundice, high bilirubin, high alanine aminotransferase or aspartate aminotransferase activity, and unfavorable outcome resulting in death of most of these patients, compared with those with isolated B19 or other hepatitis viruses infection [56]. It was hypothesized that B19 possibly may cause injury to hepatocytes independently or by producing synergistic effect when present along with other hepatitis viruses.…”
Section: Parvovirus B19 and Hepatitismentioning
confidence: 99%
“…Dwivedi et al in their study of 48 patients with FHF, divided them into three groups as those associated with (i) B19 infection alone, (ii) one or more other hepatotropic viral infection in the absence of B19 infection, and (iii) B19 coinfection with other hepatotropic viruses. They found that FHF caused by B19 and coinfection with other hepatitis viruses had severe jaundice, high bilirubin, high alanine aminotransferase or aspartate aminotransferase activity, and unfavorable outcome resulting in death of most of these patients, compared with those with isolated B19 or other hepatitis viruses infection [56]. It was hypothesized that B19 possibly may cause injury to hepatocytes independently or by producing synergistic effect when present along with other hepatitis viruses.…”
Section: Parvovirus B19 and Hepatitismentioning
confidence: 99%
“…An increasing spectrum of clinical manifestation of B19V infection has been described ( Bathla et al 2014 ), including hepatitis, which is commonly caused by hepatotropic viruses (A-E) ( Hatakka et al 2011 , Rauff et al 2011 , Huang et al 2012 ). On the basis of its DNA detection in the liver of patients with acute liver failure (ALF) associated with BM aplasia and in the serum of patients with ALF of unknown aetiology, B19V has been implicated as an aetiological agent for ALF-associated aplastic anaemia ( Aoyagi et al 1987 , Langnas et al 1995 , Bernuau et al 1999 , Abe et al 2007 , Dwivedi et al 2009 , Huang et al 2012 , Bathla et al 2014 ).…”
mentioning
confidence: 99%
“…ALF is a severe complication of acute viral hepatitis, which occurs in less than 1% of the cases and is generally caused by hepatitis A-E viruses either single or in combinations ( Dwivedi et al 2009 ). However, previous reports have demonstrated a hepatic severity significantly greater in patients with hepatotropic viruses (A and E) co-infected with B19V ( Ozcay et al 2006 , Kishore & Sen 2009 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation